Foster Kennedy Syndrome Due to Meningioma Growth during Pregnancy - Biller, Jose; Hughes, Ian; Anderson, Douglas; Lee, John; Rodriguez-Porcel, Federico (Frontiers in Neurology, 2013)
Tumors of the olfactory groove may cause unilateral optic atrophy with contralateral papilledema and anosmia (Foster Kennedy syndrome). We describe a case of a young pregnant woman with Foster Kennedy syndrome due to an olfactory groove meningioma